(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Biodiesel is a form of biofuel; diesel fuel manufactured from vegetable oils, animal fats, or recycled greases. Biodiesel is produced through a process called transesterification which involves taking naturally occurring carbon chain molecules, known as triglycerides, found in such feed stocks as seed oils and animal fats, and converting them into methyl esters, which is the chemical term for biodiesel. The conventional transesterification of the triglycerides to fatty methyl esters and glycerin is slow and not complete. During the conversion process not all fatty acid chains are turned into alkyl esters (biodiesel) reducing biodiesel quality and yield, significantly. In considering a new biodiesel facility or an upgrade of existing biodiesel plant, it is imperative that ultrasonic mixing technology be considered; it is efficient and ideal for micro scale biodiesel processing. This paper infers the efficiency of Ultrasonics for the ultrasonication of liquids and gleans that Ultrasonic cavitational mixing is the most advanced means to form fine-size emulsions at micro processing scale. The paper construes the innovative ascendancy of ‘Ultrasonic Reactor’ for micro scale production of biodiesel and demonstrates that there is a direct link between methanol droplet size, biodiesel yield, and conversion speed which makes ultrasonic reactors the most productive technology in the biodiesel industry. The paper concludes that biofuels are sustainable alternative to fossil fuels and biodiesel is a green energy source for agriculture, transport and power generation at micro level use in rural communities.